Sexing pada Ikan Brek Puntius orphoides (Valenciennes, 1863) Menggunakan Metode Truss Morfometrics - Suhestri Suryaningsih; Mahmed Sagi; Kamiso H. N.; Suwarno Hadisusanto (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2014)
The red chick barb (Puntius orphoides) is one of fresh water ichtiofauna included in family Cyprinidae found a lot in River Klawing, the biggest and richest river in Purbalingga with 18 species of fish.  The aim of this study was to find out the differences between male and female red chick barb by truss morphometrics and to find out truss morphometrics distance.  The material used were sex mature fish from River Klawing.  The variables meassured included morphometry based on truss morphometrics point, number of male and female fish.  Truss distance was then compared to the total length so that the truss distance ratio was determined.  Next, a statistical test i.e. t test was performed between the male and female fish.  The results of this study showed that the male and female red chick barb can be distinguished by truss morphometrics method.  The distance ratio to be used as diagnostic character were 11 and 24 ration of truss morphometrics distance compared found in the head, body, and tail.